Video-Based Learning as a Modern Distance Learning Method for Biology - Yanti, Febri (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
Biology, one of the fields taught in schools, is sometimes a bit difficult to convey. In biology lessons, illustrations are needed for several topics, such as body physiology, the circulatory system, the nervous system, and digestion. Therefore, it seems that the use of learning videos in the process of teaching biology will help students understand the lesson better. This study aimed to determine the use of basic educational videos as a tool for learning biology online. Literature was collected and compiled thoroughly to conduct this study. Studies have shown that basic learning videos can help teachers develop new methods for teaching biology in the classroom. The results of the study show that using basic learning videos as a medium for distance learning in biology can have a positive impact. It can improve cognitive skills and learning performance, develop interest, motivate students, and ensure that students understand the content of the lessons better.